1992
DOI: 10.1104/pp.99.4.1642
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Location of Δ1-Pyrroline-5-Carboxylate Reductase in Root/Nodule and Leaf of Soybean

Abstract: The expression of A'-pyrroline-5-carboxylate reductase (P5CR) gene was found to be higher in soybean root nodules than in leaves and roots, and its expression in roots appeared to be osmoregulated Mol Gen Genet 221: 299-305).P5CR was purified to homogeneity as a monomeric protein of 29 kilodaltons by overexpression of a soybean P5CR cDNA clone in Escherichia coli. The pH optimum of the purified P5CR was altered by increasing the salt concentration, and maximum enzyme activity was attainable at a lower pH u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 31 publications
(48 reference statements)
2
93
0
2
Order By: Relevance
“…We independently reached the Same conclusion by overexpressing soybean P5CR in transgenic tobacco (Szoke et al, 1992). We also demonstrated that the synthesis of Pro from Orn in plants proceeds via the 8-transamination of Orn to P5C and subsequent reduction to pro, and we have isolated a c~~~ clone encoding OAT.…”
Section: Treatment Of T0bac-o (Nicotiana Tabacum) Cell Cultures Withmentioning
confidence: 88%
See 3 more Smart Citations
“…We independently reached the Same conclusion by overexpressing soybean P5CR in transgenic tobacco (Szoke et al, 1992). We also demonstrated that the synthesis of Pro from Orn in plants proceeds via the 8-transamination of Orn to P5C and subsequent reduction to pro, and we have isolated a c~~~ clone encoding OAT.…”
Section: Treatment Of T0bac-o (Nicotiana Tabacum) Cell Cultures Withmentioning
confidence: 88%
“…4, lane 8). That the reaction did not result in accumulation of P5C, instead of Pro, can be explained by the observation that P5C reductase is in excess and is not a rate-limiting factor in Pro biosynthesis in plants (LaRosa et al, 1991;Szoke et al, 1992). The partially purified P5CS from E.coli expressing Vigna P5CS cDNA catalyzed the production of P5C (Fig.…”
Section: Expression Of Vigna P5cs Cdna In Transgenic Tobacco Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The observation that salinity or dehydration stress stimulated the accumulation of the transcripts for the Pro-biosynthetic genes has been interpreted to mean that the transcriptional control of these genes is important for the regulation of Pro synthesis by osmotic stress. However, 50-fold overproduction of P5C reductase in transgenic tobacco plants did not lead to increased Pro accumulation (Szoke et al, 1992), indicating that the much smaller induction of P5C reductase in NaCl-stressed plants is not likely to be of significance for the Pro accumulation.…”
mentioning
confidence: 99%